Endoscopic retrieval of a misplaced lumen‐apposing metal stent alongside a nasocystic drainage tube during endoscopic ultrasound‐guided cystogastrostomy. Issue 6 (29th August 2020) - Yang, Min Jae; Yoo, Byung Moo; Kim, Jin Hong
Abstract : Watch a video of this article